1980
DOI: 10.1016/0035-9203(80)90148-0
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphism and the problem of recrudescent parasitaemia following treatment with salicylhydroxamic acid (SHAM) in African trypanosomiasis

Abstract: The curative action of a single dose of salicylhydroxamic acid (SHAM) in combination with glycerol was investigated in mice infected with a variety of monomorphic and pleomorphic African trypanosomes. The treatment of mice infected with monomorphic members of the sub-genus Trypanozoon was always successful and resulted in a complete cure. Treatment of animals with pleomorphic infections resulted in an initial clearance of the parasitaemia which later recrudesced. Both chronic and acute infections with Trypanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The morphological variations showed by T. minasense during the course of the experimental infections reported here may be due to polymorphism as previously described in other species as (Brener 1979, Urdaneta-Morales 1983, Penin et al 1996 as well as in several African trypanosome species (Miles 1970, Hoare 1972, Ormerod et al 1974, Nantulya et al 1978, Ormerod 1979, Barry et al 1979, Evans & Brightman 1980, Vickerman 1985. There is much controversy regarding the biological significance of polymorphism in the genus Trypanosoma and the mechanisms which control it.…”
Section: Discussionmentioning
confidence: 49%
“…The morphological variations showed by T. minasense during the course of the experimental infections reported here may be due to polymorphism as previously described in other species as (Brener 1979, Urdaneta-Morales 1983, Penin et al 1996 as well as in several African trypanosome species (Miles 1970, Hoare 1972, Ormerod et al 1974, Nantulya et al 1978, Ormerod 1979, Barry et al 1979, Evans & Brightman 1980, Vickerman 1985. There is much controversy regarding the biological significance of polymorphism in the genus Trypanosoma and the mechanisms which control it.…”
Section: Discussionmentioning
confidence: 49%
“…The usual procedure to determine the nature of the suspected lesion would then be to proceed to selective renal angiography. 4 In this case the necessity for this invasive investigation of a healthy kidney was obviated by the clear tomographic radionuclide images obtained. In other patients we have found that emission tomographic imaging of the kidney can be a useful adjunct to other non-invasive studies.5…”
Section: Discussionmentioning
confidence: 95%
“…Recent work on the relapse of Trypanosoma brucei infections in rodents indicated that during remission a site of infection remains in the region of the brain.2 Such remissions induced by treatment with salicylhydroxamic acid in combination with glycerol and associated with complete removal of parasites from the blood are invariably followed by relapse parasitaemias, presumably due to reinvasion of the blood by trypomastigotes from extravascular sites. 4 We present direct evidence for the existence of a cryptic stage of the sleeping-sickness trypanosome developing in the epithelium (ependymal cells) covering the choroid plexus.…”
Section: Introductionmentioning
confidence: 88%
“…126 In contrast, the benzoate derivatives with a larger alkyl substituent (R 1 ) are expected to bind AOX in a different way, with the ester alkyl chain pointing outward from the active site ( Figure 11B). In this series, the K i decreases as the length of R 1 increases (Figure 10, 102-115; Figure 11A, [130][131][132][133][134][135][136][137][138][139][140][141][142][143][144]. Submicromolar inhibitors were obtained when the alkyl chain was greater than or equal to C6 (141)(142)(143)(144) values ( Figure 11A).…”
Section: Benzoic Acid Derivativesmentioning
confidence: 96%
“…135 Infection of animals with monomorphic BSFs resulted in complete cure 127,135 but failures were recorded when animals were infected with pleomorphic trypanosome strains, 136 despite initial clearance of parasitaemia. 136 It could be argued that these treatment failures could be due to the presence of short-stumpy forms, which also express the cytochrome-dependent (SHAM-insensitive) respiration but this is unlikely as these forms are in irreversible growth arrest until they can transform into procyclics in the tsetse fly. 118 However, the pleomorphic cell lines may have a higher preference for extravascular niches where the drug concentration may not reach the therapeutic level.…”
Section: Studies With Tao Inhibitors In In Vivo Models Of Aatmentioning
confidence: 99%